The Effect of Mat Pilates exercise on Sleep Quality of Obese Young Adults - Maria Devina Putri Elvariani; Rahmi Isma Asmara Putri; Erna Setiawati; Hexanto Muhartomo (Jurnal Kedokteran Diponegoro)
Background: Obesity currently becomes one of the world's problems that can decrease a person’s quality of sleep. Pilates exercise was found to improve sleep quality in obese patients. Pilates exercise are safe to do because they don't involve jumping and running so they avoid trauma. Mat Pilates exercise is basic exercises that are done on the floor on a mat with simpler movements.